2021
DOI: 10.1001/jamaoncol.2021.0366
|View full text |Cite
|
Sign up to set email alerts
|

Tislelizumab Plus Chemotherapy vs Chemotherapy Alone as First-line Treatment for Advanced Squamous Non–Small-Cell Lung Cancer

Abstract: IMPORTANCE This study demonstrates that tislelizumab in combination with chemotherapy is associated with improved progression-free survival (PFS) in patients with advanced squamous non-small-cell lung cancer (sq-NSCLC).OBJECTIVE To assess the efficacy and safety/tolerability of tislelizumab plus chemotherapy vs chemotherapy alone as first-line treatment for patients with advanced sq-NSCLC. DESIGN, SETTING, AND PARTICIPANTSThis open-label, randomized phase 3 clinical trial was conducted at 46 sites in China bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
238
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(245 citation statements)
references
References 28 publications
6
238
1
Order By: Relevance
“…1 . Finally, 28 eligible articles reporting 24 RCTs (23 phase 3 and 1 phase 2 trials) with 13918 patients (11698 of smokers and 2220 of never smokers) were eligible for inclusion [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] . Because one studies [10] provided pooled OS data of CheckMate-017 [9] , and -057 [11] , the pooled data were used instead of data from the individual trials in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 . Finally, 28 eligible articles reporting 24 RCTs (23 phase 3 and 1 phase 2 trials) with 13918 patients (11698 of smokers and 2220 of never smokers) were eligible for inclusion [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] . Because one studies [10] provided pooled OS data of CheckMate-017 [9] , and -057 [11] , the pooled data were used instead of data from the individual trials in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, never smokers should obtain less benefit from ICIs compared to smokers theoretically. However, this hypothesis has not been confirmed by current ICIs trials, in which inconsistent results were observed [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] . Some previous meta-analyses [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] have attempted to clarify the relationship between smoking and the efficacy of ICIs in NSCLC, while the lack of statistical power due to limitations such as small number of studies, small sample size, and few subgroup analysis prevents a final conclusion.…”
Section: Introductionmentioning
confidence: 99%
“…1 ). In total, 38 RCTs, including 41 studies with 20,173 patients with lung cancer, were included for quantitative analyses [ 6 8 , 14 48 ]. Eight studies explored the efficacy of ICI versus SOC in patients with SCLC (three studies on ipilimumab, two on atezolizumab, one on nivolumab, one about durvalumab, and one assessing tremelimumab plus durvalumab).…”
Section: Resultsmentioning
confidence: 99%
“…44 One study assessing the efficacy activity and safety of camrelizumab in patients with previously treated, advanced NSCLC negative for oncogenic drivers reported trAEs (all grades) in 69.0% of the 25 enrolled patients. 45 The phase III study 39 of tislelizumab plus chemotherapy versus chemotherapy alone as a first-line treatment for advanced squamous NSCLC demonstrated trAEs in 12.5%, 29.7%, and 15.4% of patients in the tislelizumab + paclitaxel + carboplatin, tislelizumab + nab-paclitaxel + carboplatin, and paclitaxel + carboplatin arms, respectively. No new safety signals were identified upon addition of tislelizumab to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%